Selenocysteine β-Lyase: Biochemistry, Regulation and Physiological Role of the Selenocysteine Decomposition Enzyme - Lucia A. Seale (MDPI AG, 2019)
The enzyme selenocysteine β-lyase (SCLY) was first isolated in 1982 from pig livers, followed by its identification in bacteria. SCLY works as a homodimer, utilizing pyridoxal 5’-phosphate as a cofactor, and catalyzing the specific decomposition of the amino acid selenocysteine into alanine and selenide. The enzyme is thought to deliver its selenide as a substrate for selenophosphate synthetases, which will ultimately be reutilized in selenoprotein synthesis. SCLY subcellular localization is unresolved, as it has been observed both in the cytosol and in the nucleus depending on the technical approach used. The highest SCLY expression and activity in mammals is found in the liver and kidneys. Disruption of the Scly gene in mice led to obesity, hyperinsulinemia, glucose intolerance, and hepatic steatosis, with SCLY being suggested as a participant in the regulation of energy metabolism in a sex-dependent manner. With the physiological role of SCLY still not fully understood, this review attempts to discuss the available literature regarding SCLY in animals and provides avenues for possible future investigation.